The Effectiveness of Local Wisdom-Oriented Teaching Materials to Improve the Creative Thinking Ability of Elementary School Students - Santosa, Agus Budi; Febrianto, Rohmat; Fie Dzikry, Lataniya; Ika Puspita, Ari Metalin; Adelina, Femita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The problem faced in learning in elementary school is that the teaching materials used by teachers are still limited to package books and monotonous worksheets, so that students get bored quickly and lack understanding of the context of the material. This condition has an impact on students' low creative thinking skills, especially in generating new ideas and solving problems. This study aims to analyze the effectiveness of local wisdom-oriented teaching materials in improving the creative thinking skills of elementary school students. The research method used is quantitative with a one group pretest-posttest design. The subjects of the study were 47 students in grade V of SDN 2 Karangan Trenggalek Regency who were selected through purposive sampling. The research instrument was in the form of a questionnaire on creative thinking skills consisting of 22 statements. Data analysis was carried out using a paired sample t-test with the help of SPSS. The results of the study showed a significant increase in students' creative thinking skills after the use of teaching materials based on local wisdom. In the pretest stage, 32% of students were in the high category, 68% in the medium category, and 0% in the low category. After treatment, the posttest results showed that 76% of students were in the high category, 24% in the medium category, and 0% in the low category. The hypothesis test yields a sig value. (2-tailed) 0.000 < 0.05, which means there is a significant difference between the pretest and posttest results. Thus, it can be concluded that teaching materials oriented to local wisdom are effective in improving the creative thinking skills of elementary school students.